Evaluation of a Commercial Multiplex Real-Time PCR with Melting Curve Analysis for the Detection of Mycobacterium tuberculosis Complex and Five Nontuberculous Mycobacterial Species - Keun Ju Kim; Yunhee Chang; Seung Gyu Yun; Myung-Hyun Nam; Yunjung Cho (Microorganisms)
Background: Accurate and timely diagnosis of mycobacterial infections, including Mycobacterium tuberculosis complex (MTBC) and nontuberculous mycobacteria (NTM), is crucial for effective disease management. Methods: This study evaluated the performance of the NeoPlex TB/NTM-5 Detection Kit (NeoPlex assay, Seongnam, Republic of Korea), a multiplex real-time PCR assay that incorporates melting curve analysis, compared with the line-probe assay (LPA). The NeoPlex assay could simultaneously detect and differentiate MTBC from five other NTM species: Mycobacterium intracellulare, Mycobacterium avium, Mycobacterium kansasii, Mycobacterium abscessus, and Mycobacterium massiliense. A total of 91 acid-fast bacillus culture-positive samples, comprising 36 MTBC and 55 NTM isolates, were collected from the Korea University Anam Hospital. Results: The NeoPlex assay successfully detected nucleic acids in 87 of the 91 isolates (95.6%). Notably, it identified additional mycobacterial nucleic acids not detected by the LPA in eight isolates. These findings were confirmed via DNA sequencing. The assay had 100% sensitivity and specificity for M. intracellulare, M. abscessus, M. massilense, NTM, and MTBC, whereas it had 100% specificity and sensitivity of 90.9% and 75.0% for M. avium and M. kansasii, respectively. Conclusions: These results highlight the potential of the NeoPlex assay to enhance rapid and accurate diagnosis of mycobacterial infections, particularly in settings in which prompt treatment initiation is essential.